Divergent Temporal Expression of Hyaluronan Metabolizing Enzymes and Receptors with Craniotomy vs. Controlled-Cortical Impact Injury in Rat Brain: A Pilot Study - Xing, Guoqiang; Ren, Ming; Verma, Ajay (Frontiers in Neurology, 2014)
Traumatic brain injury triggers many secondary changes in tissue biology which ultimately determine the extent of injury and clinical outcome. Hyaluronan (hyaluronic acid, HA) is a protective cementing gel present in the intercellular spaces whose degradation has been reported as a causative factor in tissue damage. Yet little is known about the expression and activities of genes involved in HA catabolism after TBI. Young adult male Sprague-Dawley rats were assigned to three groups: naïve control, craniotomy and, controlled-cortical impact-induced TBI (CCI-TBI). Four animals per group were sacrificed at 4h, 1d, 3d and 7d post CCI. The mRNA expression of hyaluronan synthases (HAS1-3), hyaluronidases (enzymes for HA degradation, HYAL 1-4 & PH20) and CD44 and RHAMM (membrane receptors for HA signaling and removal) were determined using real-time PCR. Compared to the naïve controls, expression of HAS1 and HAS2 mRNA, but not HAS3 mRNA increased significantly following craniotomy alone and following CCI with differential kinetics. Expression of HAS2 mRNA increased significantly in the ipsilateral brain at 1d and 3d post CCI. HYAL1 mRNA expression also increased significantly in the craniotomy group and in the contralateral CCI at 1d and 3d post CCI. CD44 mRNA expression increased significantly in the ipsilateral CCI at 4h, 1d, 3d and 7d post CCI (up to 25 fold increase). These data suggest a dynamic regulation and role for HA metabolism in secondary responses to traumatic brain injury.